Rain Effect to A 60 GHz Broadband Wireless System’s Performance: Study Case In Purwakarta - Endah Setyowati; Galura Muhammad Suranegara; Ichwan Nul Ichsan (JURNAL INFOTEL, 2021)
Nowadays, world wide telecommunication researchers are developing 5G technology. One of most important key technology in 5G is Milimeter-Wave (mmWave). This study measure 60 GHz broadband wireless system performance because of it’s promising potentials. However, the use of these frequencies is quite sensitive to rain that resulting an atenuation in the channel. Therefore, this study proposes two schemes to address the problem. The first scheme is the use of QAM modulation (Quadrature Amplitude Modulation) and the second scheme is an addition of LDPC (Low Density Parity Check) code techniques. From the results of this study, by using 4-QAM modulation and LDPC coderate 1/2, the broadband wireless system’s performance on the second scheme is better compared to the first scheme with 8.33 dB Signal to Noise Ratio (SNR) value to provides BER (Bit Error Rate) 10-4